Financial performance and supply chain dynamic capabilities: the Moderating Role of Industry 4.0 technologies - Eslami, Mohammad H.; Jafari, Hamid; Achtenhagen, Leona; Carlbäck, John; Wong, Alex (International journal of production research, 2024)
Industry 4.0 digital technologies are becoming indispensable for firms striving to enhance their supply chain capabilities and financial performance, but how these relationships play out in practice remains unclear. To address this issue, this study assesses the relationship between supply chain integration, supply chain agility, and financial performance from a dynamic capability perspective. Further analyses are conducted to establish whether Industry 4.0 digital technologies moderate the association between (a) supply chain integration and supply chain agility and (b) supply chain agility and financial performance. Findings based on the data pertaining to a sample of 274 Swedish manufacturing firms indicate that supply chain agility fully mediates the link between supply chain integration and financial performance. However, while Industry 4.0 digital technologies strengthen the effect of supply chain agility on financial performance, they do not moderate the relationship between supply chain integration and supply chain agility. These findings contribute to the ongoing debate regarding how digital technologies play a role in achieving competitive advantage in interplay with dynamic capabilities related to the supply chain. These findings are relevant for decision-makers, as they address the need for organisational adjustments beyond the mere introduction of Industry 4.0 technologies to fully reap their benefits.